Deep Trade Agreements and Global Value Chains: The Case of Chile, Colombia and Brazil - Zelicovich, Julieta (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The paper analyzes the influence of a country's participation within the global value chains in the adoption of deep trade agreements. To do this, the paper combines statistical analysis with the case study of three Latin American countries: Chile, Colombia and Brazil. It is argued that a high participation in global value chains may be a sufficient cause to explain the signature of such agreements, but that it does not constitute a necessary cause for it. On the contrary, other political-ideological variables, such as the orientations of the development model or the strategy of international insertion have been equally or even more important than the participation in the global value chains to explain these type of commitments in regional integration agreements.